Analisa Hubungan Penilaian Kinerja dengan Kepuasan kerja - Tomi Agus Triono (SMARTINDO, 2022)
Purpose of this article : Human Resources are the main key and have a major role in every company activity. Quality human resources will determine the success of the company in preparing plans. The purpose of this article is to find out the assessment assessments related to job satisfaction. Methodology: This study uses literature research, with the population and samples taken from the national library and google scholars, and choosing according to the topic of writing. Results: This article shows how to perform performance on job satisfaction, which results in a significant relationship and a high rate of performance, job satisfaction will follow. Keywords: Performance appraisal, Job satisfaction, Human resources